Loss of the EPH receptor B6 contributes to colorectal cancer metastasis - Mateo-Lozano, Silvia (Sci Rep, 2017)
Although deregulation of EPHB signaling has been shown to be an important step in colorectal tumorigenesis, the role of EPHB6 in this process has not been investigated. We found here that manipulation of EPHB6 levels in colon cancer cell lines has no effect on their motility and growth on a solid substrate, soft agar or in a xenograft mouse model. We then used an EphB6 knockout mouse model to show that EphB6 inactivation does not efficiently initiate tumorigenesis in the intestinal tract. In addition, when intestinal tumors are initiated genetically or pharmacologically in EphB6(+/+) and EphB6(−/−) mice, no differences were observed in animal survival, tumor multiplicity, size or histology, and proliferation of intestinal epithelial cells or tumor cells. However, reintroduction of EPHB6 into colon cancer cells significantly reduced the number of lung metastasis after tail-vein injection in immunodeficient mice, while EPHB6 knockdown in EPHB6-expressing cells increased their metastatic spread. Consistently, although EPHB6 protein expression in a series of 130 primary colorectal tumors was not associated with patient survival, EPHB6 expression was significantly lower in lymph node metastases compared to primary tumors. Our results indicate that the loss of EPHB6 contributes to the metastatic process of colorectal cancer.